2022
DOI: 10.1101/2022.11.02.22281834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A circulating proteome-informed prognostic model of COVID-19 disease activity that relies on routinely available clinical laboratories

Abstract: Defining the molecular mechanisms of novel emerging diseases like COVID-19 is crucial to identify treatable traits to improve patient care. To circumvent a priori bias and the lack of in-depth knowledge of a new disease, we opted for an unsupervised approach, using the detailed circulating proteome, as measured by 4985 aptamers (SOMAmers), of 731 SARS-CoV-2 PCR-positive hospitalized participants to Biobanque québécoise de la COVID-19 (BQC19). The consensus clustering identified six endophenotypes (EPs) present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Since aptamers were used to identify the EPs, it is expected that many of them would have significant associations with the EPs. As a result, we selected a very strict threshold of FDR < 1E-20 (two-sided MWU test, BH FDR) to identify top aptamers associated with EP6 (9). We then used the gene set characterization pipeline of KnowEnG with Reactome pathway collection (12).…”
Section: Pathway Enrichment Analysis Identified Fgfr-signaling In Sev...mentioning
confidence: 99%
See 4 more Smart Citations
“…Since aptamers were used to identify the EPs, it is expected that many of them would have significant associations with the EPs. As a result, we selected a very strict threshold of FDR < 1E-20 (two-sided MWU test, BH FDR) to identify top aptamers associated with EP6 (9). We then used the gene set characterization pipeline of KnowEnG with Reactome pathway collection (12).…”
Section: Pathway Enrichment Analysis Identified Fgfr-signaling In Sev...mentioning
confidence: 99%
“…The datasets used in this study carry rich molecular information on mechanisms of disease for COVID-19. EP6 is characterized by its enrichment in ARDS (50% vs 9% in EP1), acute kidney injury (50%) and liver dysfunction (22%) (9). Low levels of Sphingosine 1-phosphate (S1P) are associated with ARDS and have been shown to be associated with greater ICU admission and decreased survival in COVID-19 (18), and is supported by this study where S1P levels were found depleted in EP6 but enriched in EP1 (the endophenotype with the best prognostic).…”
Section: Covid-19 Ards Molecular Pathology: a Counterbalance Between ...mentioning
confidence: 99%
See 3 more Smart Citations